2007
DOI: 10.1007/s11199-006-9165-1
|View full text |Cite
|
Sign up to set email alerts
|

Schematic Responses to Sexual Harassment Complainants: The Influence of Gender and Physical Attractiveness

Abstract: This study was designed to examine the characteristics of a sexual harassment schema and its consequences using expectancy-violation theory as a framework for investigating an ostensible organizational grievance. Reactions to sexual harassment complainants were expected to be less favorable when the complainant was male than when the complainant was female. Results for the complainants of sexual harassment confirmed that men were believed less, liked less, and punished more than women. Furthermore, the tendenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 23 publications
1
29
1
Order By: Relevance
“…Further, the tendency to believe and like female complainants is stronger when they are perceived as physically attractive (Golden et al . 2001; Madera et al . 2007).…”
Section: Characteristics Of Harassers and Complainants And Perceptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the tendency to believe and like female complainants is stronger when they are perceived as physically attractive (Golden et al . 2001; Madera et al . 2007).…”
Section: Characteristics Of Harassers and Complainants And Perceptionmentioning
confidence: 99%
“…With respect to the gender of the complainant, Jones and Remland (1992) found that individuals were less tolerant of SH when the target was female rather than male. Using a framework which proposed that cognitive schema-driven expectancies lead to negative evaluations of individuals who do not conform to expected gender roles, Madera et al (2007) also found that men who complained of SH were believed less, liked less and punished more than women who complained. Further, the tendency to believe and like female complainants is stronger when they are perceived as physically attractive (Golden et al 2001;Madera et al 2007).…”
Section: Perceptions Of Shmentioning
confidence: 99%
See 1 more Smart Citation
“…they are more likely to be considered authentic or believable (e.g. Madera et al. 2007; Wuensch and Moore 2004).…”
Section: Aesthetic Value and Perks And Penaltiesmentioning
confidence: 99%
“…These expectations therefore influence the meanings and interpretations of occurrences in one's life (Walsh 1995). For instance, people's schemas concerning gender and physical attractiveness impact how they interpret and react to sexual harassment claims (Madera et al 2007). Within the current context, people's schemas are likely to influence their reactions to coach-player contact, including the acceptability of the actions and their preferred consequences thereof.…”
Section: Introductionmentioning
confidence: 99%